The Application of Criminal Law against Subsidized Solar Traders Without a Business License : A Study in the First Instance Court of the Meureudu - Nadifa, Dalilla; Mukhlis, Mukhlis; Idami, Zahratul (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
There is a regulation regarding oil and gas business activities that includes criminal sanctions is Law Number 22 of 2001 concerning Oil and Gas as amended by Law Number 11 of 2020 concerning Job Creation in conjunction with Law Number 6 of 2023 concerning the Preparation of Work and Budget Plans. Which explicitly regulates that every downstream business activity, including transportation, storage, trade, and processing, must have government permission, and that the trade in subsidized fuel can only be conducted by businesses with a trade license. Violations of these provisions are subject to criminal sanctions, indicating that the state takes the misuse of subsidized fuel management and distribution seriously. Although the law has prohibited and threatened heavy penalties and a regulatory framework is available, in reality, many people still engage in the misuse of transportation and trade licenses for subsidized diesel fuel. The purpose of this research is to explain the application of criminal penalties against subsidized solar traders without a business license in court rulings. The research method used is empirical juridical, which is legal research conducted by examining legal events in the field. The research results show that the application of criminal penalties against subsidized diesel traders without a business license in the court decisions reviewed reflects the state's commitment to protecting public interests, securing state finances, and creating order in the subsidized fuel distribution system. However, the effectiveness of criminal penalties as an instrument of law enforcement will only be optimally achieved if it is balanced with consistency in the imposition of sanctions, strengthening the supervision of subsidized fuel distribution in the field, and the continuous enhancement of public legal awareness.